Odnos in pripravljenost zaposlenih v zdravstveni negi za oskrbo pacientov s HIV/AIDS-om - Plahuta, Ana (Obzornik zdravstvene nege, 2023)
Introduction: Nurses represent a high-risk population as they come into direct contact with the body fluids of patients infected with the human immunodeficiency virus (HIV) or those with acquired immune deficiency syndrome (AIDS). The purpose of the study was to determine the professional and affective attitude of nursing staff towards patients infected with human immunodeficiency virus (HIV) or patients with acquired immune deficiency syndrome (AIDS).Methods: In the descriptive non-experimental quantitative research, the Slovene-translated questionnaire Scale of attitudes towards AIDS patients (Cronbach = 0.732) was used. 164 nursing employees from Slovenian health care institutions participated. Data collection was conducted using an online questionnaire from November 2020 to January 2021. Data were analyzed using descriptive statistics, Mann Whitney U-test and Kruskal-Wallis test. The level of statistical characteristics was taken into account (p 0.05).Discussion and conclusion: From the results of the research we can conclude that nurses in Slovenia do not express a very positive or negative attitude towards people infected with human immunodeficiency virus (HIV) or patients with acquired immune deficiency syndrome (AIDS) and are willing to offer holistic health care. In the future, we would like to focus our research on measuring general knowledge about the human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) among employees and to determine the impact of knowledge on employees' attitudes towards patients.
Keywords: Acquired Immune Deficiency Syndrome; Human Immunodeficiency Virus; infections; infekcije; medicinske sestre; nurses; sexually transmitted diseases; sindrom pridobljene imunske pomanjkljivosti; spolno prenosljive bolezni; virus humane imunske pomanjkljivost